Morphology and morphosyntax of the noun in the Amqi Amarna letters - Westhuizen, J. P. van der (Journal for semitics, 1993)
In the Amqi Amarna letters, nouns are written either in Sumerian logograms or in syllabograms. The logograms display a few inconsistencies and the syllabograms reflect a orthographic variety. Of the logograms fifty percent give no formal indication of gender or number. Identifiable masculine and feminine forms comply with standard Akkadian practice. Three cases, with different functions, are identifiable. The nominative signifies a predicative relationship, the accusative an adverbial relationship and the genitive an attributive relationship. The various features of the noun suggest that the so-called ""Amarna jargon"" was a pidgin that never quite became a creole. The logograms suggest the influence of Akkadian scribal practices and the use of syllabograms appears to be a development from Old Babylonian.